Engineering the Impossible. The Colosseum, the Great Pyramid, Chartres Cathedral - National Geographic Society (U.S.) (Burbank, CA : Warner Home Video, 2003)
Noted Egyptologist, Zahi Al-Hawass, explains current archaeological technologies such as remote controlled robots used to uncover the hidden treasures of Egypts pyramids.
Not rated.
DVD.
Closed-captioned.
Keywords: Archaeology; Video recordings for hard of hearing people; Egypt -- Antiquities; Documentary films